DAMPAK HUBUNGAN INDUSTRIAL YANG BERSIFAT KAPITALISTIK TERHADAP HARMONISASI HUBUNGAN INDUSTRIAL PENGUSAHA DENGAN PEKERJA (Studi Kasus di PT Fiscous South Pacifik Kabupaten Purwakarta) - H Gunarto (Jurnal Dinamika Hukum, 2011)
The implementation of the concept on freedom of rights for association of trade union is facing the phenomenon of liberal capitalistic global economic trends characterized by conflicting industrial relations. The problems  in this research, What are the impacts of the implementation of the concept on freedom  for association in trade unions to industrial relations which is capitalistic to the workers’ welfare?. To answer these three problems, the writer used qualitative analysis with constructivism paradigm. This study draws some conclusions as follows, the implementation of the concept on freedom for association in trade unions, which is capitalistic, affects the following: (1) the high rates on labor strike, (2) the increasing number of disputes on industrial relations between the entrepreneurs and the workers. Keywords: impact, industrial relations, capitalism